Eket Audience Perception of ‘Ekid Idediongo’ Radio Programme on Heritage FM as a Tool for Rural Development - Udoudom, Uduak Imoh; Pam, Christiana Chundung; Aondowase, Saawuan (International Journal of Education, Culture, and Society, 2023)
Recognizing the pivotal role of media in fostering societal progress, this study sought to investigate how the radio programme ‘Ekid Idediongo’ on Heritage radio contribute to the advancement of rural communities in Eket. Through a comprehensive survey method, data was collected from quantitative sources. A survey questionnaire was administered to a diverse sample of 400 respondents within Eket LGA, encompassing various demographic backgrounds. Findings from the study indicated a generally positive perception of the "Ekid Idediongo" radio programme among the Eket audience. Respondents highlighted the programme's role in raising awareness about local heritage, culture, and developmental issues. The radio programme was recognized as a valuable platform for disseminating information, fostering community engagement, and promoting social cohesion. Furthermore, the study revealed that the "Ekid Idediongo" radio programme play a significant role in knowledge dissemination, education, and empowerment of rural residents. Listeners reported an increased understanding of traditional values, history, and developmental opportunities as a result of their engagement with the programme. Notably, the radio programme emerged as a means to amplify local voices, allowing community members to actively participate in discussions on matters affecting their lives. While acknowledging the positive impact of the programme, certain challenges were identified, including limited reach in some remote areas, technological barriers, and occasional discrepancies between listener expectations and programme content. The study concluded that the "Ekid Idediongo" radio programme on Heritage 104.9FM demonstrated its potential as a potent tool for rural development in the Eket region. By fostering cultural preservation, knowledge dissemination, and community engagement, the programme contributed to the overall advancement of rural communities. The study recommended that to capture and maintain the attention of the Eket audience, 'Ekid Idediongo' programme producers should diversify its content and format.